ANALYSIS OF FINANCIAL PERFORMANCE WITH RGEC METHOD AT REGIONAL DEVELOPMENT BANK LISTED ON THE INDONESIAN STOCK EXCHANGE - Suwedy, Suwedy; Kasim, Muhammad Yunus; Husnah, Husnah (JURNAL INTERNASIONAL UNIVERSITAS TADULAKO, 2022)
This research intends to analyze the financial performance at Regional Development Banks listed on the Indonesian Stock Exchange for the 2016-2020 period using the RGEC (Risk Profile, Good Corporate Governance, Earnings, Capital). This research applied quantitative descriptive approach. Data were collected through annual financial reports published in each bank of 3 regional banks. Results of this research reveals that the financial performance at regional development Banks listed on the on the Indonesian Stock Exchange for the 2016-2020 period is identified through the Risk Profile, namely by analyzing financing risk with the NPL ratio of regional banks BJBR in the very good category, BJTM in the good category and BEKS is adequate but was not in good category in 2020 period. Liquidity risk analysis with the LDR ratio of regional banks of BJTM for the 2016 period is adequate, the 2017 period is good and in the period of 2018-2020 it is very good, the BJBR bank is in the adequate category and the BEKS bank for the 2016 and 2018 periods is good, the 2017 and 2019 periods it is in category of good, the 2020 period it is not good. Keywords: Risk Profile, Good Corporate Governance, Earning, Capital (RGEC).